Peace Psychology: Contributions from Asia - Montiel, Cristina Jayme (Archīum Ateneo, 2011)
This essay describes peace psychology in East, South, and Southeast Asia. The first section discusses direct conflict in the region and Asian ways of resolving conflict. The next section analyzes structural violence in Asia and its associated psychological dimensions. The essay closes with a preview of the future of peace psychology in Asia.